2020
DOI: 10.3390/diagnostics10010038
|View full text |Cite
|
Sign up to set email alerts
|

The Panel of 12 Cell-Free MicroRNAs as Potential Biomarkers in Prostate Neoplasms

Abstract: Prostate cancer is a global biological, medical, and social issue aggravated by the lack of reliable, highly specific, and sensitive non-invasive tests for diagnosis and staging of prostate cancer. One prospective source of biomarkers are the cell-free miRNAs present in various biological fluids. In the present study, we validated the diagnostic potential of cell-free miRNAs: miR-19b, miR-22, miR-92a, miR-378, miR-425, miR-30e, miR-31, miR-125b, miR-200b, miR-205, miR-375, and miR-660; we estimated the require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 55 publications
1
47
0
2
Order By: Relevance
“…Each RNA sample was reverse-transcribed to cDNA using the TaqMan ® MicroRNA Reverse Transcriptions Kit (PN 4366596, Applied Biosystems, USA). Single-stranded cDNA was synthesized from 2.5 μL of RNA using specific miRNA primers [ 31 , 47 , 48 ]. Samples without RNA templates were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each RNA sample was reverse-transcribed to cDNA using the TaqMan ® MicroRNA Reverse Transcriptions Kit (PN 4366596, Applied Biosystems, USA). Single-stranded cDNA was synthesized from 2.5 μL of RNA using specific miRNA primers [ 31 , 47 , 48 ]. Samples without RNA templates were used as negative controls.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 4 μL of cDNA was used as a template in a 24 μL PCR reaction. PCR products were amplified using specific primers [ 31 , 47 , 48 ] and TaqMan Universal PCR Master Mix (PN 4427788, Applied Biosystems, USA) and detected using the CFX 96TM Real-Time System (Bio-Rad, USA). The PCR reactions for each sample were run in duplicate, including blank controls without cDNA.…”
Section: Methodsmentioning
confidence: 99%
“…Primers and probes for reverse transcription and TaqMan qPCR [ 15 ] were synthesized in the Laboratory of Medicinal Chemistry (ICBFM SB RAS, Novosibirsk, Russia), their sequences are presented in Table S1 . Each reverse transcription (RT) reaction was performed in a total volume of 10 μL and contained 2.5 μL of RNA, 25-nM of each of the miRNA-specific primers, 0.5 units of RiboLockRNAse inhibitor (Fermentas, Vilnius, Lithuania), 50 units of M-MuLV–RH reverse transcriptase (BiolabMix, Novosibirsk, Russia), 2 μL of 5 × MMLV reaction buffer (250-mM Tris-HCl (pH 8.3 at 25 °C), 250-mM KCl, 20-mM MgCl 2 and 50-mM DTT) and 125-mM of each dNTP.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, we demonstrated that, selected from 84 miRNAs [ 14 ], a panel of 12 cell-free miRNAs—namely, miR-19b, miR-22, miR-92a, miR-378, miR-425, miR-30e, miR-31, miR-125b, miR-200b, miR-205, miR-375 and miR-660—allows us to classify patients with PCa and benign prostate hyperplasia (BPH) against healthy donors (HD) with 100% specificity and 100% sensitivity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently observed that both the miR-21 and K-Ras expression levels were elevated in colorectal cancer samples, suggesting that, instead of suppressing the Ras pathway, miR-21 may promote K-Ras mRNA translation during cancer development [116]. Over the last decade, the pleiotropic effects and biological significance of microRNAs in Ras signaling modulation have been established, and the use of microRNA levels as biomarkers for cancer diagnosis is under extensive research [117,118].…”
Section: Beyond the Kinase Cascades: The Link Between Ras Signaling Amentioning
confidence: 99%